Analisis Hukum Dalam Penyelenggaraan Pemerintahan Daerah Di Indonesia - Syifa Lailia; Sri Hadiningrum (Hakim, 2023)
Efficient regional government is the key to creating regional independence in Indonesia. Legal analysis of regional regimes is critical in mastering the legal framework that regulates regional independence. The constitutional regulations contained in the 1945 Constitution (UUD 1945), especially Articles 18B to 18J, are an important step in the system of regional independence. Not only that, the Regional Independence Law (UOD) and the Regional Regime Law (UPD) function significantly in regulating the principles underlying regional independence and the form of regional regimes. UOD regulates regional independence rights and allocation of authority, while UPD regulates bodies and methods for implementing regional regimes. An in-depth explanation of the determinations in the UOD and UPD helps ensure the application of regional independence is in accordance with constitutional principles and legal bases. This legal analysis is important for assessing public policy, supporting regional development, and ensuring that regional independence in Indonesia runs efficiently and in accordance with the law.